Buckling behaviour of thin concrete arch dams - Letsika, Malefetsane David (Department of Civil Engineering, 2026)
The buckling strength of concrete arch dams in the form of thin-walled shells having single and double curvature has been studied. When subjected to the hydrostatic pressure applied by the retained water, the shell undergoes mostly compressive internal reactions, which can lead in the thin shell buckling. The buckling strength of the arch dam is influenced by a variety of factors. These include the valley shape, thickness variation of the shell, the arch's geometry, and the degree of arch bulging. In this research, finite element modelling is used to assess the buckling behaviour of concrete arch dams (single and double curvature) having constant, linear, and quadratic thickness variation. The results are presented in the form of design plots that allow a safe set of design parameters to be selected while simultaneously indicating the safety factor linked with the implemented design. Several noteworthy observations have been made. It is seen that the buckling pressures drop drastically with increasing the arch dam depth (aspect ratio), with the rate of decrease diminishing as the depth increases. The bulging of the shell (rise ratio) has a notably large impact on the buckling strength of the arch dam and can thus be utilized to enhance the buckling strength of an arch. The geometric aspect of the valley shape does have a significant effect on the buckling strength with a decrease in the dam base width increasing the buckling strength significantly. the mathematical form of the arch (parabolic/circular) has no appreciable impact on its buckling strength.